(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Abstract. This work addresses topology optimization with stress constraints using the damage approach by Verbart et al. (2016) through a polygonal element discretization in the spirit of the PolyTop code ( Talischi et al., 2012b). In order to limit the maximum stress on the final structure, material in overstressed regions is considered damaged and so contributes less to the overall stiffness. Local stress constraints are replaced by one constraint requiring that the damaged and undamaged models have the same compliance. This drastically reduces the computational cost associated with the large number of constraints. Following the PolyTop philosophy, we developed a user-friendly MATLAB code using polygonal elements and the SIMP formulation for material interpolation. The popular L-bracket benchmark problem is solved to evaluate the effectiveness and efficiency of the method. The optimization is performed with the MMA algorithm ( Svanberg, 1987). We conclude by making some comparative remarks about existing formulations and the need to properly address local stress constraints. Keywords: Topology optimization, Stress constraints, Damage approach, Polygonal elements